Epidemiology and antimicrobial resistance of staphylococci other than Staphylococcus aureus from domestic animals and livestock in Africa: a systematic review - Ocloo, Remous; Nyasinga, Justin; Munshi, Zubair; Hamdy, Aisha; Marciniak, Tessa; Soundararajan, Manonmani; Newton-Foot, Mae; Ziebuhr, Wilma; Shittu, Adebayo; Revathi, Gunturu; Abouelfetouh, Alaa; Whitelaw, Andrew (Frontiers in Veterinary Science, 2022)
Staphylococci other than Staphylococcus aureus (SOSA) in animals are becoming more pathogenic and antibiotic resistant and can potentially disseminate to humans. However, there is little synthesized information regarding SOSA from animals in Africa. This systematic review provides a comprehensive overview of the epidemiology and antimicrobial resistance of the SOSA in companion animals (pets) and livestock in Africa. This systematic review (PROSPERO-CRD42021252303) was conducted according to the PRISMA guidelines, and 75 eligible studies from 13 countries were identified until August 2022. Three electronic databases (Pubmed, Scopus and Web of Science) were employed. The frequently isolated SOSA were S. epidermidis, S. intermedius, S. pseudintermedius, S. xylosus, S. chromogenes, S. hyicus, M. sciuri, S. hominis, and S. haemolyticus. Thirty (40%) studies performed antibiotic susceptibility testing (AST). Penicillin (58 %) and tetracycline (28 %) resistance were most common across all SOSA with high rates of resistance to aminoglycosides, fluoroquinolones, and macrolides in some species. Resistance to last-resort antibiotics such as linezolid and fusidic acid were also reported. Limited data on strain typing and molecular resistance mechanisms precluded analysis of the clonal diversity of SOSA on the continent. The findings of this review indicate that research on livestock-associated SOSA in Africa is lacking in some regions such as Central and Western Africa, furthermore, research on companion animals and more advanced methods for identification and strain typing of SOSA need to be encouraged.